Stamped : Racism, Antiracism, and You - Reynolds, Jason; Kendi, Ibram X. (New York, 2020)
"A history of racist and antiracist ideas in America, from their roots in Europe until today, adapted from the National Book Award winner Stamped from the Beginning"--
Section 1. 1415-1728. The story of the world's first racist ; Puritan power ; A different Adam ; A racist wunderkind -- Section 2. 1743-1826. Proof in the poetry ; Time out ; Time in ; Jefferson's notes ; Uplift suasion ; The great contradictor -- Section 3. 1826-1879. Mass communication for mass emancipation ; Uncle Tom ; Complicated Abe ; Garrison's last stand -- Section 4. 1868-1963. Battle of the black brains ; Jack Johnson vs. Tarzan ; Birth of a nation (and a new nuisance) ; The mission is in the name ; Can't sing and dance and write it away ; Home is where the hatred is -- Section 5. 1963-today. When death comes ; Black power ; Murder was the case ; What war on drugs? ; The soundtrack of sorrow and subversion ; A million strong ; A bill too many ; A miracle and still a maybe.
Includes bibliographical references (pages 257-260) and index.
Keywords: History; United States; United States; Racism; Juvenile literature; Racism; History; United States; Juvenile literature; Race relations; United States; Race relations